Impact of socio-economic background of the students on the integration of mathematics Ideas into the learning of physical electronics course - Vojo George Fasinu; Ebenezer Bonyah (Journal of Advanced Sciences and Mathematics Education, 2024)
Background: The socio-economic background of students plays an important role in shaping their mathematics skills, especially when combining mathematical ideas with learning physical electronics. However, many engineering programs do not consider students' earlier school experiences when they are admitted. Factors like family background, the type of school they went to, and their age are some reasons why it is difficult to connect mathematics to their learning in physical electronics.Aim: This research aims to study how the socio-economic background of students affects their academic performance when they bring mathematical ideas into physical electronics education.Method: The study focused on university students taking a physical electronics course in South Africa. A mixed-method approach was used, including semi-structured surveys and interviews, to collect students' opinions about combining mathematics with physical electronics.Results: The results show that students' socio-economic backgrounds affect how well they can use mathematics in their learning. The findings include: 1) Students had different levels of preparation in mathematics and physics; 2) Performance differences were found between students from rural and urban schools, 3) Those with basic knowledge of mathematics and physics performed better when combining these concepts with physical electronics.Conclusion: This study found that connecting mathematics to physical electronics helps students understand concepts better. It also introduces a model called the Socio-Economic Based Practical Reward Mathematics Integrative Model (SEB-PRMIM), which is designed to reduce the effects of socio-economic differences and improve mathematics integration in engineering education.